The Level of reading comprehension skills of the grade V pupils in Silay South : basis for enrichment reading activities - Peldonia, Vilma C. (Manila : National University, 2010)
Research on reading performance is necessary to understand the group better, their interests, needs, abilities, their learning rates, and their potentials. Understanding how they have learned, how they have reacted to learning materials, what their interests and needs were and how they have interacted with the learning environment have helped educators design a new goal for developing reading comprehension skills to the fullest.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. Introduction -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.